Incidence of Airway Obstructive Disease in Treated Patients of Pulmonary Care - Sharma, Tarun (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Airway obstructive diseases, such as chronic obstructive pulmonary disease (COPD) and asthma, are leading causes of morbidity and mortality worldwide. These conditions are characterized by airflow limitation that is usually progressive and associated with inflammation of the airways. Early diagnosis and appropriate treatment are essential for managing the symptoms and improving the quality of life for affected individuals. Aim: The purpose of this study is to determine the incidence of airway obstructive diseases in patients receiving treatment in a pulmonary care setting. Methods: A retrospective study was conducted among 200 patients attending a pulmonary care unit over the past year. Data were collected from patient medical records, and pulmonary function tests (PFTs) were reviewed. Diagnosis of airway obstructive diseases was confirmed based on clinical symptoms, radiographic findings, and PFT results. Results: The incidence of airway obstructive disease was found to be 35%, with COPD accounting for 60% of cases and asthma 40%. The majority of affected patients were elderly, and smoking history was a significant risk factor in COPD patients. Most patients with asthma had a history of allergic conditions. Conclusion: Airway obstructive diseases are prevalent among patients attending pulmonary care units, with COPD and asthma being the most common diagnoses. Early detection and management are key to improving patient outcomes and preventing further progression of the disease. Keywords: Airway obstructive disease, COPD, asthma, pulmonary care, incidence, airflow limitation.